2010
DOI: 10.1002/pts.901
|View full text |Cite
|
Sign up to set email alerts
|

Stainless steel bottles for extra virgin olive oil packaging: effects on shelf‐life

Abstract: SUMMARYThe quality changes in extra virgin olive oil afforded by the conservation in bottles of different materials were assessed in a 12-month shelf-life test. Transparent clear glass (TCG), green coloured glass (CG) and stainless steel (SS) 250-ml bottles were studied (in triplicates) alternating natural and fl uorescent light to simulate the 'in the drugstore' conditions. Every 2 months, the quality decay was assessed by monitoring some chemicals parameters and by sensory evaluation. Principal component ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Specifically, it derives from the rupture of the ester bond in 3,4‐DHPEA‐EDA, and its increase during storage is well documented in the literature . No significant results were found for lignans and flavonoids, either as function of crushing speed or storage time .…”
Section: Resultsmentioning
confidence: 94%
“…Specifically, it derives from the rupture of the ester bond in 3,4‐DHPEA‐EDA, and its increase during storage is well documented in the literature . No significant results were found for lignans and flavonoids, either as function of crushing speed or storage time .…”
Section: Resultsmentioning
confidence: 94%
“…As mentioned in the introduction, several studies instrumentally assessed the impact of the packaging and storage time on the oil quality described by relevant indices (acidity, peroxide value, K232 and K270, total phenolic content). Traditional studies on oil storage suggested that oil stored in stainless steel had better qualitative level (with significantly higher levels of phenols and lower values of the oxidative indices) than that stored in transparent clear and green colored glass [16] and that stainless and dark glass appeared to be the most adequate packaging materials compared to clear PET or clear glass [42]. However, recent studies suggest other innovative packaging materials with outstanding oxygen barriers (e.g., flexible PET with UV-blocker) can outperform glass in terms of quality parameters [14], suggesting the need to further explore the impact of new innovative solutions.…”
Section: Effect Of the Storage Time And Packaging Materials On Acceptabilitymentioning
confidence: 99%
“…Several packaging materials have been studied for oils from olives, including glass, metals (tin-coated steel) and, more recently, plastics [ 12 ]. The literature provides numerous comparisons between different materials [ 6 , 7 , 10 , 14 , 15 , 16 , 17 ]. Glass is among the most commonly used material for oil packaging [ 8 , 10 ], as it is considered the first choice as an oil container because it is impermeable to water vapor and volatile organic compounds, and it can be given light-filtering properties [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies developed a method to measure VOOs oxidation (Kanavouras et al, 2004;Cecchi et al, 2006) or mathematical predictive models (Coutelieris et al, 2006). Studies of different shape, colour (Guil et al, 2009;Rizzo, et al, 2014), and type of packaging material (Méndez et al, 2007;Parenti, et al, 2010) and their effects on the time of storage have been made. They conclude that light, oxygen, humidity and temperature (Tsimis et al, 2002;Sacchi, et al, 2008) have a negative effect in the VOOs quality preservation and product deterioration occurs when exposed to these conditions during storage.…”
Section: Recommendations For Packaging Improvementmentioning
confidence: 99%